A Novel Methicillin-Resistant Staphylococcus aureus t11469 and a Poultry Endemic Strain t002 (ST5) Are Present in Chicken in Ebonyi State, Nigeria. (19th November 2017) - Nworie, Amos; Onyema, Azi S.; Okekpa, Simon I.; Elom, Michael O.; Umoh, Nse O.; Usanga, Victor U.; Ibiam, Gideon A.; Ukwah, Boniface N.; Nwadi, Lynda C.; Ezeruigbo, Chinwe; Olayinka, Busayo O.; Ehinmidu, Joseph O.; et al.
Abstract : Background . The changing epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) from a hospital-associated pathogen to an organism commonly found in the community and in livestock reflects an organism well-equipped to survive in diverse environments and adjust to different environmental conditions including antimicrobial use. Methods . We investigated the molecular epidemiology of S. aureus and MRSA in poultry in Ebonyi State, Nigeria. Samples were collected from 1800 birds on 9 different farms within the state. Positive isolates were tested for antibiotic susceptibility and molecular typing. Results . Prevalence in birds was 13.7% (247/1800). MRSA prevalence in poultry was 0.8%. The prevalence of MRSA in broilers and layers was 1.2% and 0.4%, respectively. All tested isolates were susceptible to vancomycin. Molecular analysis of the isolates revealed 3 spa types: t002, t084, and a novel spa type, t11469. The novel spa type t11469 belonged to sequence type ST5. Conclusion . The detection of t002 in chicken suggests the presence of livestock-associated MRSA in poultry in Ebonyi State. The detection of the new spa type t11469 in poultry that has not been characterised to ascertain its pathogenic potential remains a cause for concern, especially as some were found to carry PVL genes, a putative virulence factor in staphylococcal infection.